Una Revisión de la Interpretación Económica sobre la Innovación - Luis Miguel Beristain (Journal of Technology Management & Innovation, 2009)
Theorists have employed two conflicting approaches in order to understand the economic concept of innovation: the classical theory of static equilibrium where innovation is interpreted as being exogenous to the economic system, and the dynamic equilibrium theory of endogenous technological change. Despite progress in studies and inquiries on the second model, research in and teaching of economics remain dominated by the first approach. This review discusses the differences between science, technology and innovation and implications of dynamic equilibrium theory in understanding the economy and wealth creation processes.